Fostering mental health and well‐being among workers who support refugees and asylum seekers in the Australian context. (20th April 2020) - Posselt, Miriam; Baker, Amy; Deans, Carolyn; Procter, Nicholas
Abstract: Therapists and counsellors who provide trauma‐focussed therapy and support to refugees and asylum seekers are often exposed to distressing and confronting stories of war, violence, torture, loss and grief, and other atrocities. In addition to this, working within an immigration and detention context has been reported to further contribute to experiences of burnout, vicarious trauma, and other adverse consequences of working with traumatised populations. There is a scarcity of research seeking to understand how therapists address these difficulties and maintain well‐being to help them continue in this field of work. This mixed‐methods research aimed to identify and explore factors associated with mental health and well‐being among workers, with a particular focus on the role of clinical supervision. Participants were staff ( n  = 50) who identified as providing therapeutic support to refugees and asylum seekers either in Australia or in Australian‐run detention facilities. Participants took part in an anonymous online survey which focussed on the psychological impact of their work, professional quality of life, and clinical supervision and incorporated free‐text items. Thematic analysis of free‐text data revealed four themes related to maintaining well‐being at work including relationships and support seeking; physical and contemplative practices; professional growth; and balance and boundaries. Results from the quantitative analyses revealed several variables related to supervision that were important for well‐being. In particular, the findings suggest that rapport and overall alliance with one's clinical supervisor are protective of secondary traumatic stress and depression, respectively. Important aspects of supervision were also explored in greater depth through qualitative and quantitative inquiry, increasing our understanding of the mechanisms underlying the relationship between clinical supervision and mental health and well‐being for this group.